IMPROVING THE PERFORMANCE OF LAUNDRY SMES IN TERMS OF LOCATION THROUGH DIGITAL TRANSFORMATION - Suryanto, Suryanto; Ferry Cahaya, Yohanes (Dinasti Publisher, 2022)
This study aims to improve the performance of IKM Laundry with a marketing mix mediated by digital transformation, namely fintech in the form of digital marketing, so that even with tight competition, it will be able to maintain the level of business continuity of the Laundry Industry. The data analysis method used in this research is descriptive and inferential analysis. While the inferential analysis uses the SPSS analysis tool, namely Statistical Product and Service Solution, which produces multiple linear regression, with a population of IKM Laundry business actors in Bekasi, and a sample of 100 IKM Laundry, with the sampling method of accidental sampling where the sampling is coincidentally found in at that time. The results showed that the marketing mix had a significant positive effect on the performance of IKM Laundry in Bekasi, but if it was mediated by digital marketing, the effect would be even greater. The recommended recommendation to IKM Laundry is to increase knowledge about the application of digital marketing to IKM Laundry actors so that the performance of IKM Laundry will increase.